Period determination for 1996 Adams and 2699 Kalinn by AOACM - Ambrosioni, C. (2011)
Synodic rotation periods and amplitudes are reported for 1996 Adams: 3.31138 ± 0.00006 h, 0.45 ± 0.04 mag; and2699 Kalinin: 2.9279 ± 0.0001 h, 0.24 ± 0.04 mag.